Breakthrough in Pediatric Atopic Dermatitis Therapy: The Role of Monoclonal Antibodies as a New Hope for Targeted Treatment in Children - Sosin, Julia; Pilarz, Anna; Stachowiak, Julia; Zwierzchowska, Maria; Sojka, Aleksandra; Salamon, Dariusz; Domagała, Wojciech (Quality in Sport, 2024)
Aims: Atopic dermatitis (AD) is a prevalent skin condition affecting children of all ages and ethnicities. The aim of this review paper is to explore emerging treatments for atopic dermatitis, with a focus on the latest advancements in monoclonal antibody therapy. By evaluating their benefits and potential risks, the review seeks to provide a comprehensive understanding of their efficacy and safety in managing moderate to severe AD. Highlighting recent progress in targeted therapies, this paper aims to encourage continued research into innovative, effective, and safer options that can significantly improve patients’ quality of life. Methods: A systematic review of scientific and medical literature was conducted using PubMed and Google Scholar databases. Researchers included only studies that mentioned monoclonal antibodies approved by EMA (European Medicines Agency) or that are being currently researched for use in pediatric population with AD. Results: AD is a debilitating health issue both for children and their caregivers. Advances in understanding its pathophysiology have introduced new treatment approaches. Monoclonal antibody therapies provide notable benefits for moderate to severe AD, though more pediatric-specific studies are necessary. Conclusions: Monoclonal antibody therapy appears to be a promising treatment for pediatric patients with moderate to severe AD, effectively reducing symptoms and enhancing quality of life. Despite the potential distress of injections for young children, their infrequency aids in management. Further research is required to confirm the safety and efficacy of these therapies in children. Ongoing development of new antibodies targeting various aspects of AD is crucial for improving management and outcomes.